Amor, respeito e casamento na Chapada Diamantina - Fleischer, Soraya (Afro-Ásia, 2021)
Resenha de: MEDEIROS, Melanie A. Marriage, Divorce and Distress in Northeast Brazil: Black Women’s Perspectives on Love, Respect and Kinship. New Brunswick: Rutgers University Press, 2018. 222 p.